Factors Influencing Numbers of Mycobacterium avium, Mycobacterium intracellulare, and Other Mycobacteria in Drinking Water Distribution Systems - Falkinham, Joseph O. (American Society for Microbiology, 2001)
Eight water distribution systems were sampled over an 18-month period (528 water and 55 biofilm samples) to measure the frequency of recovery and number of mycobacteria, particularly Mycobacterium avium and Mycobacterium intracellulare, in raw source waters before and after treatment and within the distribution system. The systems were chosen to assess the influence of source water, treatment, and assimilable organic carbon levels on mycobacterial numbers. Overall, mycobacterial recovery from the systems was low (15% of samples). Numbers of mycobacteria ranged from 10 to 700,000 CFU liter(−1). The number of M. avium in raw waters was correlated with turbidity. Water treatment substantially reduced the number of mycobacteria in raw waters by 2 to 4 log units. Mycobacterial numbers were substantially higher in the distribution system samples (average, 25,000-fold) than in those collected immediately downstream from the treatment facilities, indicating that mycobacteria grow in the distribution system. The increase in mycobacterial numbers was correlated with assimilable organic carbon and biodegradable organic carbon levels (r(2) = 0.65, P = 0.03). Although M. intracellulare was seldom recovered from water samples, it was frequently recovered (six of eight systems) in high numbers from biofilms (average, 600 CFU/cm(2)). Evidently, the ecological niches of M. avium and M. intracellulare are distinct.